Arabidopsis thaliana as a model plant for the study of plant-pathogen interaction between Sporisorium scitamineum and sugarcane - Silva, Mariana Marrafon Lopes da (2020)
Among the diseases that impact sugarcane productivity is smut, caused by the fungus basidiomycete Sporisorium scitamineum. Modern sugarcane genotypes are highly polyploid interspecific hybrids. This feature restricts molecular studies and functional analyses for the identification of resistance candidate genes and the proofs-of-concept. The present work evaluated the use of Arabidopsis thaliana as a model plant for S. scitamineum colonization through the use of morphological and molecular analyses. The morphological analyses demonstrated that S. scitamineum recognizes A. thaliana as a potential host allowing teliospore germination, appressorium formation and hyphal growth on leaves. The infected plants showed symptoms such as: chlorosis, accumulation of anthocyanin in the meristem and leaves, reduction in biomass, and roots ramification in advanced stages of the colonization. Molecular analyzes detected a transcription reprogramming of genes related to pathogenicity described for smuts, as well as for new effector candidates involved in S.scitamineum-sugarcane interaction. S. scitamineum also modulated the expression in A. thaliana gene associated with meristematic functions; changes also observed in S. scitamineum-sugarcane interaction. This is the first report of using a model plant to study sugarcane smut. The establishment of the pathosystem S. scitamineum- A. thaliana will allow several future applications to understand better S. scitamineum-sugarcane interaction.